Lipid/polymer-based nanocomplexes in nucleic acid delivery as cancer vaccines. Issue 8 (August 2021) - Beg, Sarwar; Almalki, Waleed H.; Khatoon, Fahmida; Alharbi, Khalid S.; Alghamdi, Saad; Akhter, Md. Habban; Khalilullah, Habibullah; Baothman, Abdullah A.; Hafeez, Abdul; Rahman, Mahfoozur; Akhter, Sohail; Choudhry, Hani
Highlights: Cancer vaccines present new therapeutic interventions for treatment. Use of functional lipids and polymers provides enhanced deliverability. Significant momentum has obtained in the success of cancer vaccine therapy. Clinical trial rate indicates reality underlying success of such vaccines. High demand on translating these vaccines require extensive regulatory oversight. Abstract : Cancer vaccines consist of nucleic acid derivatives such as plasmid DNA, small interfering RNA and mRNA, and can be customized according to the patient's needs. Nanomedicines have proven to be exceptionally good as miniaturized drug carriers, and thus they offer great advantages for delivering cancer vaccines. This review provides an overview of the literature on cancer vaccines, from their inception to current developments in the field.